The Double Bind of the Historical Novel and the Italian Postmodern Debate - Ganeri, Margherita (Spunti e Ricerche, 2016)
This article addresses the following theoretical questions: is the postmodern historical novel new or is it just the same as the nineteenth century genre, granted the obvious innovations resulting from the different historical context? Is there a link, a multiplicity of ties between the Postmodern genre and the previous ones? Or do they have nothing in common? After careful consideration of several theoretical aspects and problems, the author concludes here that the Postmodern historical novel is not a new genre, because it is defined in very much the same way in Postmodern times, as it was formerly. This definition is strongly connected with the concept of the double bind, since the historical novel is based on a contradictory mixture between truth and fiction, reality and invention. The content and form vary according to the circumstances, but the identity of this empty frame doesn’t change in space and time. Between Manzoni, Tomasi or Eco, important differences are envisaged related to both style and period, as indeed there are between Manzoni, D’Azeglio, Guerrazzi or Nievo. Genre is not a monochrome: it denotes, as the word itself signifies, a generic background in which it is possible to detect several and often hidden links.